Investment principles of the Bible: How Christian businesses cultivate wealth and attain relevance in the 21st century. (2014) - Onuoha, Luke N.
The aim of this paper is to establish the relevance of major investment principles of the Bible in today's business world. Approached from the Sowing and Reaping Principle, the paper identifies an uncertainty gap between sowing and harvest times and concludes that the Divine Presence completes the vacuum. The paper further asserts that investment in Biblical terms and today's investment methods have three important stages in common: sowing, tending and the harvest times. Finally, the paper illustrates that God's Hand is in all investments of resources whether in the Biblical times or today. The Christian investor operates by faith; the modern entrepreneur works by sight based on empirical statistics and logic. However, both achieve the bottom-line in measurable statistics. This paper would benefit not only Christian business people, but also, scholars of finance, religion and economics.